Participation, agency, and youth voice in establishing school gardens: comparing cases from Kenya and Papua New Guinea - Walker, Graham J.; Vos, Amy; Monjero, Kenneth; Sikas-Iha, Trudie; Alders, Robyn G. (Frontiers in Communication, 2024)
This community case study investigates school garden establishment in Kenya and Papua New Guinea (PNG) focussing on engagement and participation. The gardens are intersectional interventions addressing education, health and nutrition, food security, career development and life skills. We focus on engagement between implementing agencies and schools – including youth – during establishment as it influences garden governance, activity, and organisational and educational cultures going forward. Following synthesis of school garden literature, country contexts, and participation and engagement models, we present two case studies based on narrative interviews with in-country project managers, project experiences and desktop reviews. Analysis reveals distinct culturally- and project-influenced typologies of participation and engagement – Kenya’s was bottom-up driven by student participation, whereas PNG was top-down with little student participation – with differences affecting school and student garden ownership and motivation. The findings provide lessons for LMIC school garden establishment, particularly evolving project goals’ effect on engagement, managing power differentials in top-down and bottom-up models, how educational and broader culture affects student participation, need for cultural capacity building of implementing agencies, and the potential of school gardens as assets in disrupting educational norms and student-centred approaches.